2012
DOI: 10.1371/journal.ppat.1002895
|View full text |Cite
|
Sign up to set email alerts
|

Human Monoclonal Antibody HCV1 Effectively Prevents and Treats HCV Infection in Chimpanzees

Abstract: Hepatitis C virus (HCV) infection is a leading cause of liver transplantation and there is an urgent need to develop therapies to reduce rates of HCV infection of transplanted livers. Approved therapeutics for HCV are poorly tolerated and are of limited efficacy in this patient population. Human monoclonal antibody HCV1 recognizes a highly-conserved linear epitope of the HCV E2 envelope glycoprotein (amino acids 412–423) and neutralizes a broad range of HCV genotypes. In a chimpanzee model, a single dose of 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
176
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(187 citation statements)
references
References 56 publications
7
176
2
Order By: Relevance
“…Several segments of the E2 protein have been identified as key components of conformational or linear epitopes that are critical to antibody-mediated neutralization of HCV in vitro (7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Interestingly, naturally evoked antibodies and those produced in vitro that are specifically directed against a short peptide located in the E2 protein between residues 427-446, also known as epitope II, displayed one of three activities: virus neutralization, E2 binding but no neutralization, or interference with virus neutralization (15,16).…”
Section: H Epatitis C Virus (Hcv) Infection Is a Major Public Healthmentioning
confidence: 99%
“…Several segments of the E2 protein have been identified as key components of conformational or linear epitopes that are critical to antibody-mediated neutralization of HCV in vitro (7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Interestingly, naturally evoked antibodies and those produced in vitro that are specifically directed against a short peptide located in the E2 protein between residues 427-446, also known as epitope II, displayed one of three activities: virus neutralization, E2 binding but no neutralization, or interference with virus neutralization (15,16).…”
Section: H Epatitis C Virus (Hcv) Infection Is a Major Public Healthmentioning
confidence: 99%
“…Infusion of bNAbs is protective against infection in animal models of HCV (17,18), and a recent study also showed that bNAbs could abrogate established HCV infection in a humanized transgenic mouse model (19). Given the efficacy of these bNAbs in blocking HCV infection, the molecular and genetic features of bNAbs and their epitopes may serve as a useful guide for rational HCV vaccine design.…”
Section: Introductionmentioning
confidence: 99%
“…HCVpp have greatly advanced the understanding of HCV entry and neutralization by antibodies (Giang et al, 2012;Law et al, 2008;Morin et al, 2012;Osburn et al, 2014;Pestka et al, 2007). This model system has been used extensively in identifying HCV cell surface receptors required for viral entry (Bartosch et al, 2003;Cormier et al, 2004;McKeating et al, 2004;Zhang et al, 2004), and studies using HCVpp have established that neutralizing antibodies can drive evolution in vivo of HCV E1E2, leading to neutralization escape (Dowd et al, 2009;Pestka et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…These HCVcc have been used to further define viral entry pathways (Brimacombe et al, 2011;Carlsen et al, 2013;Mathiesen et al, 2015;Timpe et al, 2008) and to show that broadly neutralizing monoclonal antibodies (bNAbs) can prevent HCV infection in animal models (Forns et al, 2000;Morin et al, 2012;Youn et al, 2005). Panels of HCVcc expressing E1E2 from multiple genotypes have also been used to measure neutralizing breadth of bNAbs (Carlsen et al, 2014;Keck et al, 2008Keck et al, , 2013Law et al, 2008).…”
Section: Introductionmentioning
confidence: 99%